Enough is Enough - Cohen, Bill; Simpson, Alan (Maine Policy Review, 2014)
This is an excerpt from the 2013 William S. Cohen Lecture delivered at the University of Maine, featuring former Secretary of State Bill Cohen and Senator Alan K. Simpson, on “The State of Our Nation: Hardball vs Civility.” The full version was published in “Politics Then and Now, in Maine and the Nation," edited by Richard Barringer and Ken Palmer
Keywords: politics; U.S. Congress